Wie Lehrer_innen und Schüler_innen im Unterricht miteinander umgehen: Wiederentdeckungen jenseits von Bildungsstandards und Kompetenzorientierung - Schlickum, Christine; Leonhard, Tobias (transcript, 2014)
Every day, approximately 2.5 million hours of classroom instruction take place in Germany. How the students and teachers involved treat each other has been lost from sight in the face of educational standards and competence orientation. This volume documents the results of a qualitative-reconstructive classroom study based on work by laureates of the German Teachers' Prize with their students and class documentation. In the alleged ordinariness of classroom teaching, teachers, agents in teacher training, students, as well as parents can discover the complexity of professional demands placed on teachers as well as those moments when school shows how uplifting it can be.